Nonclosure of the Peritoneum during Appendectomy May Cause Less Postoperative Pain: A Randomized, Double-Blind Study - Huseyin Kazim Bektasoglu; Mustafa Hasbahceci; Samet Yigman; Erkan Yardimci; Enver Kunduz; Fatma Umit Malya (Pain Research and Management)
Objective. We aim to evaluate the effect of peritoneal closure on postoperative pain and life quality associated with open appendectomy operations. Methods. This is a single-center, prospective, randomized, and double-blinded study. Here, 18–65-year-old patients who underwent open appendectomy for acute appendicitis were included. Demographic data of the patients, operation time, length of hospital stay, pain scores using a 10 cm visual analogue scale (VAS) on the first postoperative day, quality of life assessment using the EuroQol-5D-5L questionnaire on postoperative 10th day, deep wound dehiscence, bowel obstruction, and mortality data were recorded. Results. In total, 112 patients were included in the study. The demographic data showed no significant difference between the groups. The median VAS score was lower in the group with open peritoneum, but this difference was not statistically significant (3 vs. 4, p=0.134). The duration of surgery was significantly shorter in the peritoneal nonclosure group (31.0 ± 15.1 vs. 38.5 ± 17.5 minutes, p=0.016). Overall complication rates and life quality test (EuroQol-5D-5L) results were similar between groups. Conclusion. Nonclosure of the peritoneum seems to shorten the duration of surgery without increasing complications during open appendectomy. Postoperative pain and life quality measures were not affected by nonclosure of the peritoneum. This trial is registered with NCT02803463.